2022
DOI: 10.1101/2022.02.04.22270468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily heart rate variability biofeedback training decreases locus coeruleus MRI contrast in younger adults

Abstract: As an arousal hub region in the brain, the locus coeruleus (LC) has bidirectional connections with the autonomic nervous system. Magnetic resonance imaging (MRI)-based measures of LC structural integrity have been linked to cognition and arousal, but less is known about factors that influence LC structure and function across time. Here, we tested the effects of heart rate variability (HRV) biofeedback, an intervention targeting the autonomic nervous system, on LC MRI contrast and sympathetic activity. Younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…For instance, engaging in a bout of moderate intensity exercise tends to increase processing speed (McMorris & Hale, 2015 ), which may be due to activation of the locus coeruleus (LC) and associated noradrenergic activity (McMorris, 2016 ). As we report elsewhere (Bachman et al, 2022 ), among younger adults the Osc+ intervention significantly decreased left LC magnetic resonance imaging contrast. a measure reflecting locus coeruleus magnetic properties.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, engaging in a bout of moderate intensity exercise tends to increase processing speed (McMorris & Hale, 2015 ), which may be due to activation of the locus coeruleus (LC) and associated noradrenergic activity (McMorris, 2016 ). As we report elsewhere (Bachman et al, 2022 ), among younger adults the Osc+ intervention significantly decreased left LC magnetic resonance imaging contrast. a measure reflecting locus coeruleus magnetic properties.…”
Section: Discussionsupporting
confidence: 85%
“…LC contrast is influenced by the accumulation of neuromelanin, a by-product of catecholamine metabolism (Keren et al, 2015 ). Among the younger cohort, relative to the Osc− condition, the Osc+ condition also decrease cAMP-responsive element binding protein (CREB)-regulated gene expression in circulating blood cells, an index of sympathetic nervous system signaling (Bachman et al, 2022 ). Thus, one possibility that should be examined in future research is whether the Osc+ intervention influences processing speed via its suppression of noradrenergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a previously established semi-automatic analysis procedure to extract individual LC and SN– VTA intensity values from structural imaging data (for a detailed description and validation, see [87], for applications, see [88,89,127]; for an independent validation see [91]). The following procedure was performed separately for TP1 and TP2 imaging data.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is worth noting that in studies performed in adults, LC-MRI signal has been shown to be associated with LC-related cognitive and autonomic functions, even in the absence of brain pathology [ 160 , 161 , 162 , 171 , 172 ]. Furthermore, in a very interesting recent pre-print, Bachman and colleagues found that LC signal can vary in follow-up assessments, after autonomic biofeedback training [ 173 ]. Those studies suggest that LC-MRI parameters are associated with LC functioning and plasticity, even in the absence of morphological alterations, which might be a potential scenario occurring in NdD.…”
Section: Future Perspectivesmentioning
confidence: 99%